Hostel management for foreign workers [compact disc] : problems in non-purpose built building - 387723 Chong, Voon Ping (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Pengurusan Fasiliti) - Universiti Teknologi Malaysia, 2005